THE EFFECT OF SPINACH CONSUMPTION ON INCREASING HAEMOGLOBIN IN PREGNANT WOMEN - Umu Qonitun; Suhartatik, Suhartatik (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Anemia is a symptom of a lack of red blood cells due to low hemoglobin levels. Based on the performance assessment report of the Tuban Regency Senori Community Health Center  East Java Indonesia in 2022, it was found that 36.65% of pregnant women experienced anemia. This shows that there are still many pregnant women who experience anemia and need treatment. The aim of this research is to determine the effect of spinach consumption on increasing hemoglobin levels in pregnant women. Method: quasi experiment with One Group Pretest-Posttest design. The sample in this study was 16 pregnant women with anemia in the Senori Community Health Center Tuban Regency East Java Indonesia, who met the inclusion criteria. The research instrument used an observation sheet to determine hemoglobin levels in the blood before and after consuming green spinach, an easy touch Hb level check tool. Data were analyzed using paired T-test. Result : The average Hb level of pregnant women before the intervention was 10.20 gr% and after the intervention was 11.18 gr%, the results of the paired t-test showed a significance value = 0.000, so the significance value (2-tailed) < α (0 .05) which shows that there is an effect of spinach consumption on increasing hemoglobin levels in pregnant women. Conclusion : There is an effect of spinach consumption on increasing Hb levels in pregnant women. Integrated ANC activities are expected to be carried out routinely so that pregnant women who experience anemia can be detected early and health workers can provide explanations to pregnant women about the dangers of anemia during pregnancy and the consumption of spinach and its benefits.